Disease Activity and Related Variables in Patients with Psoriatic Arthritis - Fatma Gül YURDAKUL; Filiz ESER; Hatice BODUR; Ülker GÜL; Müzeyyen GÖNÜL; Işıl Deniz OĞUZ (Archives of Rheumatology, 2014)
Objectives: This study aims to investigate the disease activity and related variables in patients with psoriatic arthritis (PsA). Patients and methods: Fifty patients with PsA, who were diagnosed based on the Classification Criteria for Psoriatic Arthritis (CASPAR), were included. The patients were divided into five groups according to the Moll and Wright criteria. The disease was assessed using the Disease Activity Score for Reactive Arthritis (DAREA) index, the Disease Activity Score including 28 joints (DAS28), the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and the Psoriasis Area and Severity Index (PASI). In the laboratory tests, the erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) levels were determined, and a functional assessment was performed using the Health Assessment Questionnaire (HAQ). Pain was evaluated via the Visual Analog Scale for Pain (VAS-Pain), and the Patient Global Assessment (PaGA) and Physician Global Assessment (PhGA) results were recorded. Results: The asymmetrical oligoarticular type of PsA was seen most often (n=28, 56%), with the distal interphalangeal predominant type of PsA (n=2, 4%) and arthritis mutilans (n=2) being the least frequent. There were statistically significant correlations between the DAREA score and the CRP and ESR levels as well as the VAS, PaGA, DAS28, and HAQ scores. The BASDAI scores had statistically significant relationships with the PaGA and PhGA in the group with spondylitis. Conclusion: We determined that the DAREA, as a disease activity index, was well correlated with both the laboratory and clinical assessment findings in patients with PsA. Furthermore, the DAS28 is a helpful adjunctive measurement instrument for assessing PsA activity, and the BASDAI may prove to be more valuable for patients with spondylitis.